HAK WARGA PASIEN PROLANIS UNTUK MENDAPATKAN PELAYANAN KESEHATAN BERDASARKAN UNDANG – UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DI KLINIK RAHMATIKA SEMARANG - Muhammad Zahrawan Qurrotaa’yun; Muzayanah (Jurnal Pengabdian Kepada Masyarakat Media Ganesha, 2023)
Health services are a primary need in the life of every human being and it is the right to obtain them, therefore everyone needs a healthy body condition to be able to carry out daily activities in order to achieve a prosperous life. In addition to this, health is a human right and one of the elements of social welfare that must be realized in accordance with the ideals of the Indonesian nation, as referred to in Pancasila and the 1945 Constitution. Health services are a manifestation of the implementation of U.U. Number 36 of 2009 Concerning Health, so that it is the need and right of every Indonesian citizen. Furthermore, that every activity in an effort to maintain and improve the highest degree of public health, is carried out based on the principles of non-discrimination, participatory and sustainable in order to shape Indonesia's human resources, as well as increase the nation's resilience and competitiveness for national development. This can be realized by carrying out development which must be based on health insights in the sense that national development must pay attention to the health of the community and of course it must be the responsibility of all parties, both for the Government and for the community. This activity is an internship/KKL implementation that must be taken by every student at FHB UNISBANK Semarang who goes directly to the community in order to apply the knowledge gained at the Faculty of Law and Language UNISBANK Semarang. This internship/KKL activity is carried out by the author at the RAHMATIKA Primary Clinic in Semarang which is a health facility that provides health services to the community in general and Prolanis Patient Residents in particular who need health services for themselves and for their families. The implementation of this internship activity apart from carrying out work practices at the RAHMATIKA Pratama Clinic in providing health services to Prolanis Patient Residents, is also carried out by providing legal counseling on "Rights of Prolanis Patient Citizens to Obtain Health Services Based on U.U. Number 36 of 2009 concerning Health". The legal counseling carried out is a Field / Internship work practice activity carried out by the Author together with the Apprentice Supervisor who is the responsibility of Academics in implementing Government Programs in order to provide services to the community to understand and understand that every citizen has guaranteed rights based on the 1945 Constitution, especially in The provisions regarding CHAPTER XA which regulates human rights, especially in article 28 letter H and U.U. Number 36 of 2009 concerning Health.